Evaluasi dan Strategi Pengembangan Bisnis “Cokelat Pena” - Vira Setya Puspa Anggreani; Mochamad Malik Akbar Rohandi; Rezi Muhamad Taufik Permana (UNISBA Press, 2024)
Abstract. Culinary as part of the creative industry is currently emerging in many big cities. The culinary beverage business that is growing rapidly in Indonesia is processed chocolate. Cokelat Pena has also made innovations regarding processed chocolate drinks which prioritize its beneficial aspects for society. So it becomes an instant and brewed drink that is efficacious and has many benefits, which combines herbal plants such as vetiver (Vetiveria Zizanoides) and cinnamon (Cinnamomum Verum) for health in it and is known as herbal chocolate